Muka Air Optimum Pada System Of Rice Intensification (SRI) - Nur Aini Iswati Hasanah; Budi Indra Setiawan; Chusnul Arif; Slamet Widodo (Jurnal Irigasi, 2017)
Controlling water table is the way to manage water in SRI paddy field. Farmers tend to apply different water table depend on their local water management practices. It may have different effect on plant growth that can be seen in the number of tillers. In this study, tiller development of SRI paddy was studied by using experimental pots under various water tables treatments. The water table is controlled by using mariotte tube and set at -12, -7, -5, -3, 0, and +2 cm from the soil surface. The result shows that soil moisture (Ɵ) were fluctuated due to intermittent irrigation and water table treatment. It affects the tiller growths rate that varied with average value 0.21-0.29 tiller/day. The first tiller appears at 18 days after transplanting (DAT). The tillers number keep increasing until reaching the highest number (around 63 to 72 DAT). This empirical study showed that setting water table at -5 cm under soil surface in SRI paddy cultivation is the best to reach high tiller number, and highest land and water productivity compare to another water table treatments. Consistency in producing tiller from beginning tiller production until the end of cultivation season could be seen from this treatment.